Genetic Analysis of Calf Survivability in Gir Crossbreds (Indian Journal of Animal Production and Management, 2024)
Data of Gir crossbred calves, maintained at  Research cum Development Project on Cattle,  Mahatma Phule Krishi Vidyapeeth, Rahuri, for a  period from 2005 to 2019 was collected to study  effect of genetic and non-genetic factors on  survivability traits of calf. The traits studied were  cumulative survivability within 0 to 15 days, 0 to 30  days, 0 to 90 days, 0 to 180 days and 0 to 365 days.  The least square means of cumulative survivability  per cent of Gir crossbred calves at 0 to 15, 0 to 30,  0 to 90, 0 to 180 and 0 to 365 days were  83.27±2.16, 75.40±2.57, 62.29±2.99, 53.96±3.16  and 52.16±3.17, respectively. The period of birth  had significant (P
Keywords: calves; survivability; non-genetic factors; genetic; cumulative